CCAFS climate change and social learning strategy - CGIAR Research Program on Climate Change, Agriculture and Food Security (2013)
The CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) is implementing a uniquely innovative and transformative research program that addresses agriculture and food security in the context of climate variability, climate change and uncertainty about future climate conditions.